2004
DOI: 10.1051/0004-6361:20041200
|View full text |Cite
|
Sign up to set email alerts
|

Properties and environment of the molecular complex near Holmberg IX

Abstract: Abstract. This paper is aimed at providing new insight into the nature and origin of the molecular complex situated near the line of sight toward Holmberg IX in the M 81 group of galaxies. The first high resolution CO maps of the complex as well as single dish 13 CO(1-0), 12 CO(3-2) and millimeter continuum observations and the results of a survey of 12 CO in the region are presented. These data together with the available HI, optical and X-ray observations are analyzed to study the properties and environment … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…This suggests that these stellar systems have been assembled from pre-enriched material. This is consistent with the conclusions of Boone et al (2005) towards Holmberg IX are similar to those found in the discs of spiral galaxies. The distribution of the stellar clumps along an H I tail, tracing the densest clouds within the gaseous arm, indicates that these systems may have been assembled out of gas pulled from one of the large interacting galaxies in the group.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that these stellar systems have been assembled from pre-enriched material. This is consistent with the conclusions of Boone et al (2005) towards Holmberg IX are similar to those found in the discs of spiral galaxies. The distribution of the stellar clumps along an H I tail, tracing the densest clouds within the gaseous arm, indicates that these systems may have been assembled out of gas pulled from one of the large interacting galaxies in the group.…”
Section: Discussionsupporting
confidence: 93%
“…4; additional dark features are stars not subtracted well). Eleven sources (1-11) were previously identified by Miller & Hodge (1994) and one by Boone et al (2005) (source 12). 2 Thus, we found nine new sources (13-21).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Nevertheless, we identified 21 objects with significant Hα emission. Eleven sources (1-11) were previously identified by Miller and Hodge (1994) and one by Boone et al (2005) (source 12). Thus, we found nine new sources (13-21) -not catalogued HII regions.…”
Section: Discussionmentioning
confidence: 99%